Risk Factors and Outcomes of Late-Onset Bacterial Sepsis in Preterm Neonates Born at < 32 Weeks' Gestation - Shah, Jyotsna; Jefferies, Ann L.; Yoon, Eugene W.; Lee, Shoo K.; Shah, Prakesh S.; on behalf of the Canadian Neonatal Network (American Journal of Perinatology, 2015)
Objective This study aims to identify the incidence, risk factors, and outcomes of late-onset sepsis in preterm neonates in Canadian neonatal intensive care units (NICUs).Study Design This retrospective analysis included preterm infants born at < 32 weeks' gestation and admitted to 29 NICUs in the Canadian Neonatal Network during the years 2010 and 2011. Infants were classified into three groups: no infection, gram-positive infection, and gram-negative infection. Late-onset sepsis was defined as positive blood and/or spinal fluid cultures after 3 days of birth. Risk factors and the primary outcome of mortality or bronchopulmonary dysplasia (BPD) were compared between the groups.Results Out of the 7,509 neonates, 6,405 (85%) had no infection, 909 (12%) had gram-positive, and 195 (3%) had gram-negative infections. Lower gestation, higher Score for Neonatal Acute Physiology, version II scores, the presence of central catheters for > 4 days, parenteral nutrition for > 7 days, and prolonged duration of nothing by mouth were associated with late-onset sepsis. After controlling for confounders, the odds ratio (OR) of mortality/BPD were higher in infants who had gram-negative (OR 2.79, 95% confidence interval [CI] 1.96–3.97) and gram-positive (OR 1.44, 95% CI 1.21–1.71) sepsis as compared with no infection.Conclusions Bacterial late-onset sepsis in very preterm neonates was associated with mortality and BPD. Neonates with gram-negative sepsis had the highest risk of adverse outcomes as compared with gram-positive sepsis or no sepsis.
Keywords: infant; premature; nosocomial infection; late-onset sepsis; mortality; bronchopulmonary dysplasia